Sensorimotor and proprioceptive exercise programs to improve balance in older adults: a systematic review with meta-analysis - Silvo Pšeničnik Sluga; Ziga Kozinc (PAGEPress Publications, 2024)
The primary aim of this study was to systematically review and meta-analyze the impact of sensorimotor and proprioceptive exercises on balance in older adults. We also sought to define how researchers describe proprioceptive and sensory-motor training and their respective protocols. The review was conducted following the PRISMA guidelines, with searches performed in March 2023. Both authors carried out independent searches using the PubMed and PEDro databases. From a total of 320 identified records, 12 studies were deemed eligible for meta-analysis after screening and removal of duplicates. The average PEDro score was 5.11 ± 1.11 indicating overall fair quality of studies.  Common outcome measures included the Berg balance scale, Timed up and go test, Tinetti balance scale, Functional reach test and various single-leg stance tests. All outcomes were significantly improved by the interventions (standard mean difference = 0.65 - 1.29), with little difference between proprioceptive and sensorimotor training. However, the quality of evidence ranged from "very low" to "low" based on GRADE guidelines, suggesting further high-quality studies are needed. This review underscores the potential benefits of sensorimotor and proprioceptive exercises for enhancing balance in older adults, while also highlighting the ambiguity and inconsistency regarding the usage of the terms proprioceptive and sensorimotor training.